2013
DOI: 10.1158/1078-0432.ccr-12-3243
|View full text |Cite
|
Sign up to set email alerts
|

Exposure–Response Relationships of the Efficacy and Safety of Ipilimumab in Patients with Advanced Melanoma

Abstract: Purpose: This retrospective analysis was conducted to characterize ipilimumab exposure-response relationships for measures of efficacy and safety in patients with advanced melanoma.Experimental Design: Data were pooled from 498 patients who received ipilimumab monotherapy at 0.3, 3, or 10 mg/kg in 1 of 4 completed phase II clinical trials. The relationships between steady-state ipilimumab trough concentration (Cminss), complete or partial tumor response (CR or PR), and safety [immune-related adverse events (ir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
147
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(153 citation statements)
references
References 17 publications
6
147
0
Order By: Relevance
“…With ipilimumab treatment in melanoma patients, C minss was identified as a significant predictor for the occurrence of an immune-related AE (irAE). 94 The probability of experiencing grade ࣙ3 irAEs increased with increasing ipilimumab exposure at the median C minss for doses of 0.3, 3, and 10 mg/kg; however, analyses of the relationship between exposure and safety with approved PD-1 and PD-L1 inhibitors have found a flat relationship. In patients with melanoma who received nivolumab 0.1 to 10 mg/kg every 2 weeks, the risk of time to first grade ࣙ3 drug-related AEs S37 and AEs leading to discontinuation did not increase with average concentration at steady state (C avgss ).…”
Section: Exposure-safety Relationshipmentioning
confidence: 99%
“…With ipilimumab treatment in melanoma patients, C minss was identified as a significant predictor for the occurrence of an immune-related AE (irAE). 94 The probability of experiencing grade ࣙ3 irAEs increased with increasing ipilimumab exposure at the median C minss for doses of 0.3, 3, and 10 mg/kg; however, analyses of the relationship between exposure and safety with approved PD-1 and PD-L1 inhibitors have found a flat relationship. In patients with melanoma who received nivolumab 0.1 to 10 mg/kg every 2 weeks, the risk of time to first grade ࣙ3 drug-related AEs S37 and AEs leading to discontinuation did not increase with average concentration at steady state (C avgss ).…”
Section: Exposure-safety Relationshipmentioning
confidence: 99%
“…[67][68][69][70] A meta-analysis including 1265 patients from 22 clinical trials found that the risk of developing an immune-related adverse event (any grade) was threefold higher with ipilimumab 10 mg/kg versus 3 mg/kg. 68 In EORTC 18071, grade 3 to 4 adverse events were more common with ipilimumab versus placebo (54% vs 25%), as were immune-related adverse events (grade 3, 37% vs 2%; grade 4, 6% vs <1%).…”
Section: High-dose Ipilimumabmentioning
confidence: 99%
“…The cut-off for maximal binding for CD80 and CD86 has been reported as target concentrations of 20 μg/mL and 3 μg/mL, respectively. [34] Recent data have also shown that the activity of ipilimumab may also involve selective depletion of regulatory T cells within tumor lesions, which suggests that target concentrations may not reflect the clinical endpoints sufficiently. [35] The results from the phase III trial (ClinicalTrials.gov registry number NCT01515189) will help us fully understand the mechanism of action and dose-effect relationship for ipilimumab.…”
Section: Transl Clin Pharmacolmentioning
confidence: 99%